SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN GURU TERBAIK MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING DAN TOPSIS - Nimatus Sholehah; Febri Maspiyanti (JURNAL ILMIAH INFORMATIKA, 2020)
Teacher is the initial peak of the creation of a nation with qualified young generation, both in academic and non-academic. Perintis 1 Depok Vocational School does not have a supportive system for selecting the best teachers yet. In carrying out this process, Depok Perintis 1 Vocational School still records data manually where the data is still recorded in a text book and uses Ms. Excel so determining the results of the best teacher selection takes quite a long time. Therefore, a web application for the selection of the best teachers is needed so it can facilitate the process of assessment and preservation of any existing data. In determining the selection of high achieving teachers in SPK, the Simple Additive Weighting (SAW) method and Topsis method are used to obtain more accurate results. From the two methods, the results show that the second teacher had the highest result, 74.4 in SAW method calculation and 0.77661 in Topsis method calculation.